Arhaeological evidence for seismic activity in Butrinti (SW Albania)and neotectonics of the area - PAVLIDES, S.; KOCIU, S.; MUKELLI, P.; HYSENl, A.; ZOUROS, N. (Bulletin of the Geological Society of Greece, 2001)
This is a preliminary study of the neotectonics and the historical seismic destruction imprinted on the archaeological site of Butrinti (SW Albania). Two fault sets surround and intersect both the limestone hill with the archaeological site and the area around it. A normal N-S trending fault is located along the NW of Butrinti hill with an observable length of 1 km and a maximum vertical displacement of 3-4m. The southern part of the hill is confined by a steep tectonic scarp, trending E-W to NE-SW, which represent the continuity of the transcurrent (right-lateral strike-slip) fault of Northern Corfu. Fault planes parallel to this fault have been observed inside the archaeological site. The continuous subsidence of part the ancient city, the presence of evaporates diapirs and their continuous vertical movement allows us to conclude that these faults are still active. Cracks crossing special foundation stone elements of archaeological buildings and other types of dislocation were the main criteria to evident seismic damage in this study. The catastrophes of the Hellenistic-Roman theatre of Butrinti and the surrounding monuments dated to the 3rd-4th century AD should be attributed to the seismic activity triggered by the reactivation of these faults during late Roman-early Byzantine time (358 AD). Another seismic event affecting Byzantine monuments is also probable (1153).